2008
DOI: 10.1007/s10577-008-1258-y
|View full text |Cite
|
Sign up to set email alerts
|

Separation and maintenance of normal cells from human embryonic stem cells with trisomy 12 mosaicism

Abstract: Human embryonic stem cells (hESCs) are pluripotent and hold great promise as useful tools in basic scientific research and in the field of regenerative medicine. However, several studies have recently reported chromosomal abnormalities such as gains of chromosomes 12, 17 and X in hESCs. This genetic instability presents an obstacle in the application of hESCs as sources of cell therapies. We found that trisomy 12 was correlated with changes in hESC colony morphology during hESC maintenance. In this study, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…hPSCs are prone to genetic instablity 17 . For example, trisomy of chromosome 12 is often seen with continuous culture of pluripotent stem cells and in certain cancer cells 18 . Recent studies have shown that “adapted” cells that carry karyotypic abnormalities can display characteristic cell behaviors that differ from those of karyotypically normal hESCs 19 .…”
Section: Resultsmentioning
confidence: 99%
“…hPSCs are prone to genetic instablity 17 . For example, trisomy of chromosome 12 is often seen with continuous culture of pluripotent stem cells and in certain cancer cells 18 . Recent studies have shown that “adapted” cells that carry karyotypic abnormalities can display characteristic cell behaviors that differ from those of karyotypically normal hESCs 19 .…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of aneuploid occurring in hESCs still remains unknown. Maybe it is very rare, but there have already been several reports about trisomic in hESCs [25,26]. The presence of trisomic in the hESCs suggests that the aneuploid may not be eliminated by further development after embryo implantation.…”
Section: Discussionmentioning
confidence: 99%
“…5h,i). However, we also observed sex chromosome aneuploidy in one A-hiPSC clone and trisomy 12 in one A-iPSC-ZSCAN10 clone, which are common chromosomal alterations in pluripotent stem cell culture and more likely to have been introduced by in vitro expansion and not by A-iPSC-specific reprogramming 44,45 .…”
Section: Resultsmentioning
confidence: 60%